Dental Health Labyrinth Game Education to Improve Dental and Oral Health Knowledge in Elementary School Students - Fitratunisa, Mufida Afiah; Lestari, Syifa Yulia (Journal Center of Excellent : Health Assistive Technology, 2025)
Background: Elementary school children are aware of the learning and understanding process. Therefore, it is important to improve dental health knowledge. The use of appropriate media for promoting dental and oral health is very effective if it is adjusted to the age of fifth grade elementary school students. One of the educational media used is a maze game that is adapted to convey dental health information interactively. So that it can be used in promotional activities which are one of the UKGS programs to improve dental health knowledge. Objective: This study aims to analyze dental and oral health knowledge before and after the dental health labyrinth game education in elementary school students. Method: The research design used a quasi-experiment with a pretest and posttest design with one group design. Sampling in this study used a purposive sampling technique with a sample size of 62 respondents. The instrument used a questionnaire and Dental health labyrinth media. Data analysis was conducted using the Wilcoxon test. Results: The results showed that dental health knowledge increased, from 32 students (51.6%) in the sufficient category to 62 students (100%) in the good category. The average increase in knowledge before and after education was 78.39 to 98.06 with statistical test results p = 0.000 (p <0.05). Conclusion: Dental health labyrinth game education is effective increasing dental health knowledge in elementary school students